Evaluation of the implementation of COVID-19 prevention and control in the work area of Kalibaru Kulon health center - Novie Erva Fauziyah; Ayik Mirayanti Mandagi; Thinni Nurul Rochmah; Moh. Basri (Journal of Community Empowerment for Health, 2022)
In early 2020, the COVID-19 pandemic spread rapidly to all countries, including Indonesia. This problem prompted the government to immediately make efforts to suppress the spread of COVID-19. Public Health Centers are at the front line in breaking the chain of transmission of COVID-19 because they are located in every sub-district and have a regional concept. This research is a participatory observational study and was conducted from July 6 – 31, 2020. Researchers at the same time as volunteers coordinated with the Public Health Centers and evaluated the implementation of COVID-19 Prevention and Control in the Work Area of Kalibaru Kulon Health Center. The evaluation was done based on the guidelines for the Prevention and Control of COVID-19 by analyzing and interpreting the data and developing a descriptive narrative. The results of the evaluation have shown the suitability of the guidelines with the implementation of the rapid test program, screening COVID-19 at check point posts, and ‘Sekolah Tangguh & Pondok Tangguh’. But, there are still some indicators that are not following the guidelines, especially in the implementation of rapid test program and ‘Sekolah Tangguh & Pondok Tangguh’. The conclusion from the evaluation of the implementation of Kalibaru Kulon Health Center program in making efforts to prevent and control COVID-19 is that the implementation of the program has not been optimal when compared to existing guidelines so that more efforts need to be made such as increasing the role of the government as the developer of policies, which is supported by public awareness to realize community independence in the health sector.